Chronic effects of stroke on hip bone density and tibial morphology: a longitudinal study. Issue 2 (February 2016) - Lam, F.; Bui, M.; Yang, F.; Pang, M.
Abstract Summary The study aimed to quantify the long-term effects of stroke on tibial bone morphology and hip bone density. Only the trabecular bone mineral density and bone strength index in the hemiparetic tibial distal epiphysis showed a significant decline among individuals who had sustained a stroke 12–24 months ago. Introduction This study aims to determine the changes in bone density and morphology in lower limb long bones during a 1-year follow-up period and their relationship to muscle function in chronic stroke patients. Methods Twenty-eight chronic stroke patients (12–166 months after the acute stroke event at initial assessment) and 27 controls underwent bilateral scanning of the hip and tibia using dual-energy X-ray absorptiometry and peripheral quantitative computed tomography, respectively. Each subject was re-assessed 1 year after the initial assessment. Results Twenty stroke cases and 23 controls completed all assessments. At the end of the follow-up, the paretic tibial distal epiphysis suffered significant decline in trabecular bone density (−1.8 ± 0.6 %, p  = 0.006) and bone strength index (−2.7 ± 0.6 %, p  < 0.001). More severe decline in the former was associated with poorer leg muscle strength (ρ  = 0.447, p  = 0.048) and motor recovery (ρ  = 0.489, p  = 0.029) measured at initial assessment. The loss in trabecular bone density remained significant among those whose stroke onset was 12–24 months ago (p  < 0.001), but not among those whose stroke onset was beyond 24 months ago (p  > 0.05) at the time of initial assessment. The changes of outcomes in the tibial diaphysis, except for cortical bone mineral content on the non-paretic side (−1.3 ± 0.3 %, p  = 0.003), and hip bone density were well within the margin of error for precision. Conclusions There is evidence of continuous trabecular bone loss in the paretic tibial distal epiphysis among chronic stroke patients, but it tends to plateau after 2 years of stroke onset. The steady state may have been reached earlier in the hip and tibial diaphysis.